Let m = -8 + 11. Let p be m + 7 - 31. Solve -p*b + 2*b = -5 for b.

1

Suppose -2*b - 7 + 33 = 0. Solve -3*k + 1 = b for k.

-4

Let u© be the third derivative of c6120 - c512 - 5*c36 + c2. Let o be u(5). Let z = 8 + o. Solve z*j + 1 = -2 for j.

-1

Let h = 5 + -2. Let q be h/2*(2 + 0). Suppose -4*t + l + 49 = 0, 5*t + q*l - 55 = 2. Solve -4*c - t = -7*c for c.

4

Let k(g) = -g**2 + 13*g - 8. Let w be k(12). Solve 6 + 14 = w*v for v.

5

Let s be ((-6)/(-9)*-1)/(4/(-12)). Let l be 1 - 6 - (1 - 0). Let v = -4 - l. Solve s*b = v - 12 for b.

-5

Suppose -c + m - 5 = -6*c, m = c + 5. Suppose c = -0*a + 3*a - 6. Let h be 4 + (a - (-12)/(-3)). Solve -j = -h*j for j.

0

Let x be (-4)/(-16) - 28. Suppose -z + 4 + x = 0. Solve -3*q + z = -q for q.

2

Let l(s) = s + 12. Let u be l(-5). Let r = 12 + -7. Let y(o) = 3*o - 6. Let q be y®. Solve 0 = -4*w + u + q for w.

4

Let h be 0/2 + (-2 - 3). Let r = h - -7. Suppose r*w + 4*v - 4 = 0, 5*w + 4*v - 10 = 3*v. Solve -w*t - 1 - 3 = 0 for t.

-2